Experimental analysis of tool wear when drilling carbon fibre composite (CFC) without cutting fluid, with cutting fluid and with a pre-cryogenically cooled tool - Dahnel, Aishah Najiah; Barnes, Stuart; Bhudwannachai, Pipat (Trans Tech Publications, 2013)
Machining of Carbon Fibre Composites (CFCs) particularly drilling, is frequently employed in industry especially when dealing with joining, assembly and structural repair of the parts. However, the nature and heterogeneous structure of CFCs often results in rapid wear of the cutting tool. This research studied the relationship and compared the effect of drilling a CFC plaque without cutting fluid, with conventional cutting fluid and with cryogenic cooling at constant cutting speed of 94 m/min and feed rate of 0.065 mm/revolution using tungsten carbide twist drill. The conventional cutting fluid was supplied continuously to the drill and the CFC plaque during the drilling cycle; while for the cryogenic cooling tests, the drill tip was immersed in liquid nitrogen for 10 and 30 seconds prior to drilling the CFC. It was found that the tool wear increased with the increasing number of drilled holes at all machining conditions. After drilling of 325 holes, the largest tool wear observed was 181 μm which was produced when drilling the CFC plaque with conventional cutting fluid. The corresponding tool wear for drilling with cryogenic cooling was 164 μm and the smallest tool wear of 155 μm was observed during dry drilling. Dry drilling produced the smallest tool wear because the heat generated reduced the strength of the CFC, particularly polymer matrix. Therefore, this situation led to easier machining of CFC materials; consequently reduced the wear of the tool.